NEATH − III. A molecular line survey of a simulated star-forming cloud - Priestley, Felix; Clark, P C; Glover, Simon; Ragan, S E; Fehér, O; Prole, L R; Klessen, R S (Monthly notices of the Royal Astronomical Society, 2024)
We present synthetic line observations of a simulated molecular cloud, utilizing a self-consistent treatment of the dynamics and time-dependent chemical evolution. We investigate line emission from the three most common CO isotopologues (12CO, 13CO, C18O) and six supposed tracers of dense gas (NH3, HCN, N2H+, HCO+, CS, HNC). Our simulation produces a range of line intensities consistent with that observed in real molecular clouds. The HCN-to-CO intensity ratio is relatively invariant with column density, making HCN (and chemically similar species such as CS) a poor tracer of high-density material in the cloud. The ratio of N2H+ to HCN or CO, on the other hand, is highly selective of regions with densities above 10 22 cm -2 and the N2H+ line is a very good tracer of the dynamics of high volume density > 10 4 cm -3 material. Focusing on cores formed within the simulated cloud, we find good agreement with the line intensities of an observational sample of prestellar cores, including reproducing observed CS line intensities with an undepleted elemental abundance of sulphur. However, agreement between cores formed in the simulation, and models of isolated cores which have otherwise-comparable properties, is poor. The formation from and interaction with the large-scale environment has a significant impact on the line emission properties of the cores, making isolated models unsuitable for interpreting observational data.
Veröffentlicht: 11. Juni 2024
Gesehen am 19.11.2024